2009
DOI: 10.1080/00365540903095358
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the incidence, prevalence and clinical burden of hepatitis C over time in Italy

Abstract: Our objective was to estimate HCV clinical burden over time in Italy. A national age-specific HCV prevalence in 1995 was obtained from studies conducted in general population samples and intravenous drug users. Age profile of new HCV infections and trend of incidence since 1985 were derived from a database of reported acute HCV infections. These incidence and prevalence data were used to estimate HCV burden from 1950 to 2030 by mathematical modelling. Different rates of HCV related liver disease progression we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 58 publications
3
31
1
3
Order By: Relevance
“…97 In France, HCV HCC related mortality is projected to increase through 2020 98 . With few exceptions 99 , most countries have yet to experience the peak burden of HCV infection. Fortunately, these projections do not account for improved efforts to control morbidity and mortality by prevention and treatment.…”
Section: Figurementioning
confidence: 99%
“…97 In France, HCV HCC related mortality is projected to increase through 2020 98 . With few exceptions 99 , most countries have yet to experience the peak burden of HCV infection. Fortunately, these projections do not account for improved efforts to control morbidity and mortality by prevention and treatment.…”
Section: Figurementioning
confidence: 99%
“…Intravenous drug use, beauty treatment, hospitalization, surgical intervention, dental therapy and having more than two sexual partners were in decreasing order the most frequently reported risk factors [15]. However, the epidemiology of HCV infection has undergone substantial changes over the past two decades, with a progressive decrease in incidence and a shift in risk factors [16]. In particular, the most recent decrease in incidence rates could be due to changes in injecting behavior among IVDUs and information campaigns on HIV/AIDS.…”
Section: Current Knowledge and Limitations On General Hcv Epidemiologmentioning
confidence: 99%
“…In Italy, mathematical modeling suggested that accelerated spread of HCV occurred from 1945 to 1969 (earlier than in the United States), with prevalence peaking in 1970, and HCV-related cirrhosis and deaths peaking from 1980 to 1985. When compared with 2005, cirrhosis and deaths in 2025 may be halved [13]. Lastly, in Australia, mathematical modeling estimated that HCV incidence peaked in 1999 and has fallen since then from 14,000 to 9700 infections by 2005, mostly from reduced injection drug use.…”
Section: Disease Burdenmentioning
confidence: 95%